Anaerobic Digestion 2019
DOI: 10.5772/intechopen.82815
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Responses to Different Operating Practices for Biogas Production Systems

Abstract: Biogas production requires a number of different microbial groups that work in a synchronized and closely interacting manner. For bioreactors constructed to maximize waste treatment and energy production, it is crucial to manage this process in a way that secures the growth and activity of these microorganisms, as otherwise there is a great risk of process failure. However, the microbiome has a remarkable ability to adapt to various conditions related to substrate composition and operating conditions, thus sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 259 publications
(339 reference statements)
2
69
0
3
Order By: Relevance
“…Apart from fermentative bacteria, the order Thermoanaerobacteriales, including several known syntrophic acetate-oxidizing bacteria e.g., Caldanaerobacter and Alkaliphilius, was shown to increase [32]. The methanogenic archaeal community mainly consisted of members of the genera Methanosarcina [33][34][35]. The Methanobacteria, Methanomicrobiales, and/or Methanomassiliicoccaceae members were also observed in certain AD-processes featuring a high organic load, depending on other prevailing conditions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from fermentative bacteria, the order Thermoanaerobacteriales, including several known syntrophic acetate-oxidizing bacteria e.g., Caldanaerobacter and Alkaliphilius, was shown to increase [32]. The methanogenic archaeal community mainly consisted of members of the genera Methanosarcina [33][34][35]. The Methanobacteria, Methanomicrobiales, and/or Methanomassiliicoccaceae members were also observed in certain AD-processes featuring a high organic load, depending on other prevailing conditions [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bacteroides was enriched in M1 and Defluviitoga was enriched in M2. Both these genera are known to degrade both smaller and more complex carbohydrates (Maus et al, 2015;Westerholm and Schnürer, 2019). Defluviitoga has previously been observed in both one-stage and two-stage processes, but its occurrence in the present study was somewhat unexpected as, to our knowledge, this genus has so far only been observed in thermophilic conditions (Giuliano et al, 2014;Fontana et al, 2018).…”
Section: Hydrolysis Of Complex Biomassmentioning
confidence: 41%
“…[30][31][32]60 The uncultured proteiniborus detected in this study might be related to P. ethanoligenes and P. indolifex, which had been found in the thermophilic biogas reactor. 33,61 However, the involvement of uncultured clostridium in biogas production has not been reported. The relative proportion of uncultured bacterium accounted for more than 33.35% of bacterial species ( Figure 4).…”
Section: Syntrophic Microbial Species That Grow In Formate Synthetimentioning
confidence: 99%